Isidore's Etymologiae at the school of Canterbury. (26th November 2014) - Porter, David W.
Abstract: This article demonstrates that some 180 of the 2, 400 text glosses in the 'Leiden Glossary' derive from an epitome of the Etymologiae. A reconstruction of this lost source shows that it consisted of abbreviated entries from all twenty of Isidore's books, with selected books heavily glossed in Old English. Mirroring the encyclopedic scope of the Etymologiae, this seventh-century epitome was extensively excerpted by glossary-compilers and gave thousands of English words their first written form.